PERMODELAN STRUKTUR MATRIAL BETON PT SARANG LAKSANA MANDIRI - putra, hengky ayang; Arista, Anggia (Computer Science and Industrial Engineering, 2020)
PT. Sarang Laksana Mandiri is a manufacturing company in the manufacture of readymix concrete located in Kabil Raya - Punggur - Batam, which has the brand name Batam Concrete, PT Sarang Laksana Mandiri received complaints from consumers on PT Sarang Laksana Mandiri's k-300 products, consumer complaints that PT Sarang Laksana Mandiri's k-300 concrete product is not included in the concrete compressive strength quality criteria so that when tested, the k-300 product does not reach 100% K 300 concrete, while the k-300 Concrete criterion is concrete that can withstand a weight of 300 kg / Cm2 after the concrete is dry and is one month or 28 days old. This study aims to determine the K-300 concrete design that is Indonesian Standard, conduct experiments to make samples of K-300 products according to Indonesian Standards, determine the decision of K-300 products from Civil Engineering experts and concrete experience experts with AHP (Analytical Hierarchy Process) method and methods SAW (Simple Additive Weighting) with the criteria of dry concrete length, concrete compressive strength, concrete slump and material cost, aims to choose the best concrete modeling modeling. the two methods used show the same results in choosing the best kimson design in each criteria, the Kimson AHP Method is globally superior to all criteria with an average value of 0.40, Herry Huang the second priority has a value of 0.32, the third priority Dwi has a value of 0.15, then Eman has a value of 0.13 and the Keputusa SAW method shows Kimson superior to the alternative A value globally from all criteria with an average value of 0.74, then Herry Huang the second priority value of B has a value of 0.71, the third priority value of C Dwi has a value of 0.68, then Eman value D has a value of 0.58.